2005
DOI: 10.1517/14712598.5.1.137
|View full text |Cite
|
Sign up to set email alerts
|

12th Annual Congress of the European Society of Gene Therapy

Abstract: The 2004 European Society of Gene Therapy (ESGT) meeting took place at Tampere Hall in Finland and highlighted advances in a variety of topics, including cancer, zinc-fingers, stem cells, small interfering RNA (siRNA), microRNA, and recent developments of non-viral and viral vectors. This meeting was attended by 513 participants from 32 countries, and included 106 oral and 224 poster presentations. One of the aims of this meeting was to take a critical look at gene therapy and the prospects for the future. Se-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several studies showed the importance of let-7's role in a poor outcome of cetuximab-treated metastatic CRC patients [ 102 , 103 ]. Also, let-7a-mediated regulation of K-Ras expression was fi rst described in lung cancer [ 104 ].…”
Section: Micrornas As Drugsmentioning
confidence: 99%
“…Several studies showed the importance of let-7's role in a poor outcome of cetuximab-treated metastatic CRC patients [ 102 , 103 ]. Also, let-7a-mediated regulation of K-Ras expression was fi rst described in lung cancer [ 104 ].…”
Section: Micrornas As Drugsmentioning
confidence: 99%